A method for improving struvite crystallization rate and purity based on ultrasonic pretreatment

CN120364892BActive Publication Date: 2026-10-30SHANGHAI JIAOTONG UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510544235.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-04-28
Publication Date
2026-10-30
Estimated Expiration
2045-04-28

AI Technical Summary

Technical Problem

[0006]针对现有垃圾焚烧厂渗滤液主流处理工艺中的氮磷营养元素高值化协同回收效率低、产品纯度不高等问题,本发明提出了一种基于超声波预处理的提高鸟粪石结晶速率和纯度方法

Benefits of technology

[0027]利用本发明的超声波预处理,可以使垃圾渗滤液中的SS(悬浮固体)作为后续鸟粪石结晶的晶核,从而很好的提高鸟粪石的生成速率。通过本发明提供的方法,可使回收得到的鸟粪石结晶的反应时间从原来未进行超声波预处理的45min缩短至15-25min。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120364892B_ABST
    Figure CN120364892B_ABST
Patent Text Reader

Abstract

The application discloses a method for improving struvite crystallization rate and purity based on ultrasonic pretreatment, and belongs to the technical field of environmental engineering. The method for improving struvite crystallization rate and purity based on ultrasonic pretreatment comprises the following steps: homogenizing landfill leachate, carrying out high-power ultrasonic treatment under the power of 150-250 W, then carrying out low-power ultrasonic treatment under the power of 20-50 W, and obtaining ultrasonic treatment liquid; adjusting the pH value of the ultrasonic treatment liquid to 9-10, then adding a magnesium source to carry out struvite crystallization reaction, and generating struvite crystallization. By using the ultrasonic pretreatment, the SS (suspended solid) in the landfill leachate can be used as a crystal nucleus for subsequent struvite crystallization, so that the crystallization rate of struvite is improved. By using the method, the purity of the recovered struvite crystallization can reach more than 90%, and the struvite crystallization reaction time is shortened from 45 min to 15-25 min.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of environmental engineering technology, and in particular to a method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment. Background Technology

[0002] Incineration is one of the most common methods for municipal solid waste treatment, and most municipal solid waste still relies on incineration technology for processing. Before being sent to the incinerator, waste is usually stored in a storage pit for 3 to 7 days to reduce its moisture content and increase its calorific value. This step results in leachate equivalent to 5% to 28% of the total waste volume. Survey data from multiple waste incineration plants show that the leachate from these plants contains high concentrations of pollutants such as organic carbon and nitrogen. The concentrations of chemical oxygen demand (COD), total nitrogen, and ammonia nitrogen can reach 33,000-89,000 mg / L, 1,300-3,300 mg / L, and 1,000-3,000 mg / L, respectively. The quality of leachate from waste incineration plants is affected by factors such as waste composition, initial moisture content, ambient humidity, and storage pit temperature, as shown in Table 1.

[0003] Table 1 Typical water quality characteristics of leachate from waste incineration plants

[0004] pH value 5.0-8.0 TOC (mg / L) 15000-80000 COD (mg / L) 33000-89000 <![CDATA[BOD5(mg / L)]]> 16000-30000 <![CDATA[NH3-N(mg / L)]]> 1000-3000 <![CDATA[NO2-N(mg / L)]]> 20-400 TN (mg / L) 1300-3300 TP (mg / L) 50-150

[0005] Existing landfill leachate treatment technologies mainly include pretreatment, flocculation and sedimentation, biochemical treatment, strong chemical oxidation, MBR, ultrafiltration, nanofiltration, and reverse osmosis, combining physicochemical and biological treatment methods. This technology has achieved relatively good results in treating landfill leachate, enabling stable discharge that meets standards. However, it fails to effectively recover and utilize the large amounts of nitrogen and phosphorus nutrients contained within. Struvite recovery technology is an effective method for recovering nitrogen and phosphorus from leachate. Its basic principle is to generate struvite through a chemical precipitation reaction, thereby achieving simultaneous removal and recovery of nitrogen and phosphorus. However, leachate often contains interfering substances such as organic matter and heavy metals, which can affect struvite formation; for example, SS (suspended solids), the content of which in incineration plant leachate generally exceeds 2000 mg / L, significantly impacting struvite formation. Furthermore, in the struvite crystallization process, crystal nuclei play a crucial role, and their formation and properties directly affect the crystallization rate, crystal size, and morphology. Overall, the removal efficiency of struvite (MAP) precipitation technology has not yet reached its maximum or optimal level. The crystallization purity and reaction rate of struvite still need to be further improved. Exploring how to enhance the high-efficiency utilization of struvite precipitation is of great significance. Summary of the Invention

[0006] To address the problems of low efficiency in the high-value synergistic recovery of nitrogen and phosphorus nutrients and low product purity in existing mainstream leachate treatment processes for waste incineration plants, this invention proposes a method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment. The leachate is homogenized and then subjected to high-power ultrasonic treatment, followed by low-power ultrasonic treatment. The pH of the ultrasonically pretreated leachate is then adjusted to 9-10, and a magnesium source is added to initiate the struvite crystallization reaction, generating struvite crystals.

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] One of the technical solutions of this invention is to provide a method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment, comprising the following steps:

[0009] After homogenizing the landfill leachate, it is subjected to high-power ultrasonic treatment at 150-250W, and then subjected to low-power ultrasonic treatment at 20-50W to obtain ultrasonically treated liquid.

[0010] The pH of the ultrasonic treatment solution is adjusted to 9-10, and then a magnesium source is added to carry out the struvite crystallization reaction to generate struvite crystals.

[0011] Preferably, the initial concentration of ammonia nitrogen in the landfill leachate is 1000-3000 mg / L, and the initial concentration of total phosphorus is 50-150 mg / L.

[0012] Preferably, the high-power ultrasonic treatment time is 10-15 minutes.

[0013] Preferably, the low-power ultrasonic treatment takes 5-10 minutes.

[0014] Preferably, when adjusting the pH value of the ultrasonic treatment solution, a sodium carbonate-sodium bicarbonate buffer solution is used.

[0015] Preferably, the sodium carbonate and sodium bicarbonate buffer solution is a 0.1 mol / L sodium carbonate and sodium bicarbonate buffer solution, prepared by:

[0016] (1) Preparation of 0.1 mol / L sodium carbonate solution: Dissolve 10.6 g of sodium carbonate powder gradually in 100 mL of pure water;

[0017] (2) Preparation of 0.1 mol / L sodium bicarbonate solution: Dissolve 8.4 g of sodium bicarbonate powder in 100 mL of pure water;

[0018] (3) Take 50 mL of the sodium carbonate solution from step (1) into a beaker, and then slowly add the sodium bicarbonate solution from step (2). Use a pH meter to monitor the pH value and adjust it to the desired target range by adding sodium bicarbonate solution. Store the prepared buffer solution at room temperature or in a refrigerated environment for later use.

[0019] Preferably, the magnesium source is selected from one or more of magnesium chloride, magnesium sulfate, and magnesium carbonate.

[0020] Preferably, the molar ratio of magnesium in the magnesium source to total phosphorus in the ultrasonic treatment liquid is (0.8-1.2):(1.0-1.5).

[0021] More preferably, the molar ratio of magnesium in the magnesium source to total phosphorus in the ultrasonic treatment liquid is 1.1:1.5.

[0022] Preferably, the crystallization reaction time of the struvite is 15-25 minutes.

[0023] The second technical solution of the present invention provides an application of the above-mentioned method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment in the high-value recovery of nitrogen and phosphorus from landfill leachate.

[0024] The technical principle of this invention is as follows:

[0025] This invention first utilizes high-power ultrasound to pretreat the leachate. On one hand, this directly degrades some small suspended solid particles, reducing their impact as impurities on the purity of subsequent struvite crystallization. On the other hand, ultrasonic treatment breaks down larger suspended solid particles with a diameter of over 100 micrometers, transforming them into smaller particles and altering their surface properties. The struvite gradually transforms from a plate-like layered structure into a porous structure with honeycomb-like pores. The pore sites provided lower the energy barrier for struvite nucleation, regulate crystal growth direction, stabilize initial crystal nuclei, and promote crystal formation rate and product purity. Then, low-power ultrasound is used to treat the leachate, preventing the agglomeration of the previously generated small suspended solid particles, resulting in more uniform struvite crystal shape and particle size. Simultaneously, ultrasound treatment can enhance the vibrational intensity of functional groups on the surface of SS. After ultrasound treatment, the vibrational peaks of amino (-NH2) and nitro (-NO2) groups on the SS surface are significantly enhanced. The lone pair electrons of the amino nitrogen in amino (-NH2) make it easy to participate in nucleophilic substitution or addition reactions, and it has protonated electrostatic adsorption properties. It can combine with protons to form ammonium salts and can also adsorb PO4. 3-The presence of anionic groups promotes the nucleation of struvite crystals. Nitro groups (-NO2) are strong electron-withdrawing groups that can significantly alter the charge distribution on the surface of molecules or materials through inductive and conjugation effects. Nitro-modified suspensions can be adsorbed onto the crystal nucleus surface via electrostatic interactions, serving as nucleation sites to regulate crystal growth direction and promote directional crystallization. This invention uses ultrasonic pretreatment to make SS (sulfuric acid) a heterogeneous crystal nucleus for struvite crystallization, accelerating the crystallization rate. Furthermore, this invention uses one or more of magnesium chloride, magnesium sulfate, and magnesium carbonate as an exogenous magnesium source for the struvite crystallization reaction, while simultaneously adjusting the pH of the reaction system to 9-10, further favoring struvite crystal formation.

[0026] The beneficial technical effects of the present invention are as follows:

[0027] By utilizing the ultrasonic pretreatment of this invention, suspended solids (SS) in landfill leachate can serve as nuclei for subsequent struvite crystallization, thereby significantly increasing the struvite formation rate. The method provided by this invention reduces the reaction time for recovered struvite crystallization from 45 minutes without ultrasonic pretreatment to 15-25 minutes.

[0028] Compared to conventional struvite recovery technologies (such as the study on the recovery of ammonia nitrogen from kitchen waste biogas slurry by struvite crystallization combined with bio-flocculation and slag removal, Yang Dekun; and the study on the recovery of nitrogen and phosphorus by struvite crystallization using seawater as a magnesium source, Zhang Ping et al.), this invention, through ultrasonic pretreatment, can effectively improve the purity of subsequent struvite crystallization, increasing the purity from the conventional 80% to over 90%, and has great application value. Attached Figure Description

[0029] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0030] Figure 1 This is a flowchart illustrating the treatment process of landfill leachate in various embodiments of the present invention. Detailed Implementation

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.

[0032] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, are also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0033] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. It should be noted that any aspects of this invention not described in detail are conventional practices in the art and are not the focus of this invention.

[0034] The terms “comprising,” “including,” “having,” “containing,” etc., used in this invention are all open-ended terms, meaning that they include but are not limited to.

[0035] All raw materials used in the following embodiments and comparative examples of the present invention are commercially available products.

[0036] The preparation method of the 0.1 mol / L sodium carbonate-sodium bicarbonate buffer solution in the various embodiments and comparative examples of the present invention is as follows:

[0037] (1) Preparation of 0.1 mol / L sodium carbonate solution: Dissolve 10.6 g of sodium carbonate powder gradually in 100 mL of pure water;

[0038] (2) Preparation of 0.1 mol / L sodium bicarbonate solution: Dissolve 8.4 g of sodium bicarbonate powder in 100 mL of pure water;

[0039] (3) Take 50 mL of the sodium carbonate solution from step (1) into a beaker, and then slowly add the sodium bicarbonate solution from step (2). Use a pH meter to monitor the pH value and adjust it to the desired target range by adding sodium bicarbonate solution. Store the prepared buffer solution at room temperature or in a refrigerated environment for later use.

[0040] Figure 1 This is a flowchart illustrating the treatment process of landfill leachate in various embodiments of the present invention.

[0041] The treatment of landfill leachate using the mainstream treatment system mentioned in the embodiments and comparative examples of this invention refers to sequentially performing a two-stage AO+MBR system followed by nanofiltration treatment.

[0042] Example 1

[0043] A method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment, comprising the following steps:

[0044] The leachate from a waste incineration plant in Shanghai was selected, with a COD of 42600 mg / L, ammonia nitrogen of 2000 mg / L, and total phosphorus of 150 mg / L. The leachate was introduced into an equalization tank, where a submersible agitator was installed at the bottom at a stirring speed of 50 rpm for continuous agitation. The leachate was then uniformly introduced into an ultrasonic pretreatment device, where it underwent high-power ultrasonic treatment for 12.5 minutes at 250 W, followed by low-power ultrasonic treatment for 10 minutes at 25 W. The effluent from the ultrasonic treatment was then introduced into a struvite crystallization reaction tank. The pH of the system was adjusted to 9.5 using a 0.1 mol / L sodium carbonate-sodium bicarbonate buffer solution. Magnesium chloride was then added to achieve a magnesium to phosphorus molar ratio of 1.1:1.5, and the crystallization reaction was carried out for 15 minutes to generate struvite crystals.

[0045] Tests showed that after treatment with this process, the phosphorus recovery rate in landfill leachate can reach 96.8%, the reaction rate of struvite crystallization is increased by 62.5% compared with no ultrasonic pretreatment (Comparative Example 4), and the purity of the generated struvite crystals is as high as 92.47%.

[0046] Example 2

[0047] A method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment, comprising the following steps:

[0048] The leachate from a waste incineration plant in Shanghai was selected, with a COD of 53,300 mg / L, ammonia nitrogen of 3,000 mg / L, and total phosphorus of 80 mg / L. The leachate was introduced into an equalization tank, where a submersible agitator was installed at the bottom at a stirring speed of 50 rpm for continuous agitation. The leachate was then uniformly introduced into an ultrasonic pretreatment device, where it underwent high-power ultrasonic treatment for 15 minutes at 250 W, followed by low-power ultrasonic treatment for 5 minutes at 50 W. The effluent from the ultrasonic treatment was then introduced into a struvite crystallization reaction tank. The pH of the system was adjusted to 10 using a 0.1 mol / L sodium carbonate-sodium bicarbonate buffer solution. Magnesium sulfate was then added to achieve a magnesium to phosphorus molar ratio of 1.2:1.0, and the crystallization reaction was carried out for 20 minutes to generate struvite crystals.

[0049] Tests showed that after treatment with this process, the phosphorus recovery rate in landfill leachate can reach 91.36%, the reaction rate of struvite crystallization is increased by 53.49% compared with no ultrasonic pretreatment (Comparative Example 5), and the purity of the generated struvite crystals is as high as 90.8%.

[0050] Example 3

[0051] A method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment, comprising the following steps:

[0052] The leachate from a waste incineration plant in Shanghai was selected, with a COD of 48,100 mg / L, ammonia nitrogen of 2,000 mg / L, and total phosphorus of 50 mg / L. The leachate was introduced into an equalization tank, where a submersible agitator was installed at the bottom at a stirring rate of 50 rpm for continuous agitation. The leachate was then uniformly introduced into an ultrasonic pretreatment device, where it underwent high-power ultrasonic treatment for 110 minutes at 200W, followed by low-power ultrasonic treatment for 7.5 minutes at 20W. The effluent from the ultrasonic treatment was then introduced into a struvite crystallization reaction tank. The pH of the system was adjusted to 9 using a 0.1 mol / L sodium carbonate-sodium bicarbonate buffer solution. Magnesium carbonate was then added to achieve a magnesium to phosphorus molar ratio of 0.8:1.0, and the crystallization reaction was carried out for 25 minutes to generate struvite crystals.

[0053] Tests showed that after treatment with this process, the recovery rate of phosphorus in landfill leachate can reach 89.9%, the reaction rate of struvite crystallization is increased by 44.44% compared with no ultrasonic pretreatment (Comparative Example 3), and the purity of the generated struvite crystals is as high as 90.3%.

[0054] Comparative Example 1

[0055] The only difference from Example 1 is that the high-power ultrasonic treatment is omitted, and only low-power ultrasonic treatment is performed, with the treatment time modified to 117.5 min. In this case, the struvite crystallization reaction time is 18 min.

[0056] Testing showed that after treatment with this process, the phosphorus recovery rate in the landfill leachate was 94.3%, the reaction rate of struvite crystallization was increased by 55.0% compared with no ultrasonic pretreatment (Comparative Example 4), and the purity of the generated struvite crystals was 90.34%.

[0057] Comparative Example 2

[0058] The only difference from Example 2 is that the low-power ultrasonic treatment is omitted, and only high-power ultrasonic treatment is performed, with the high-power ultrasonic treatment time modified to 117.5 min. In this case, the reaction time for struvite crystallization is 22 min.

[0059] Testing showed that after treatment with this process, the phosphorus recovery rate in the landfill leachate was 90.60%, the reaction rate of struvite crystallization was increased by 48.84% compared with no ultrasonic pretreatment (Comparative Example 5), and the purity of the generated struvite crystals was 89.16%.

[0060] Comparative Example 3

[0061] The only difference from Example 3 is that the low-power ultrasonic treatment and high-power ultrasonic treatment are omitted, and the leachate in the conditioning tank is directly introduced into the struvite crystallization reaction tank. The reaction time for struvite crystallization is 45 minutes.

[0062] Testing revealed that after treatment using this process, the phosphorus recovery rate in the landfill leachate was only 86.42%, and the purity of the generated struvite crystals was 81.54%.

[0063] Comparative Example 4

[0064] The only difference from Example 1 is that the low-power ultrasonic treatment and high-power ultrasonic treatment are omitted, and the leachate in the conditioning tank is directly introduced into the struvite crystallization reaction tank. The reaction time for struvite crystallization is 40 minutes.

[0065] Testing revealed that after treatment using this process, the phosphorus recovery rate in the landfill leachate was only 88.31%, and the purity of the generated struvite crystals was 84.47%.

[0066] Comparative Example 5

[0067] The only difference from Example 2 is that the low-power ultrasonic treatment and high-power ultrasonic treatment are omitted, and the leachate in the conditioning tank is directly introduced into the struvite crystallization reaction tank. The reaction time for struvite crystallization is 43 minutes.

[0068] Testing revealed that after treatment using this process, the phosphorus recovery rate in the landfill leachate was only 87.92%, and the purity of the generated struvite crystals was 83.29%.

[0069] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.

Claims

1. A method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment, characterized in that, The steps are as follows: After homogenizing the landfill leachate, it is subjected to high-power ultrasonic treatment at 150-250W, and then subjected to low-power ultrasonic treatment at 20-50W to obtain ultrasonically treated liquid. The pH of the ultrasonic treatment solution was adjusted to 9-10, and then a magnesium source was added to carry out the struvite crystallization reaction to generate struvite crystals. The high-power ultrasonic treatment time is 10-15 minutes; The low-power ultrasonic treatment time is 5-10 minutes. By utilizing the ultrasonic pretreatment of this invention, suspended solids in landfill leachate can serve as nuclei for subsequent struvite crystallization, thereby significantly improving the struvite formation rate.

2. The method according to claim 1, characterized in that, The initial concentration of ammonia nitrogen in the landfill leachate is 1000-3000 mg / L, and the initial concentration of total phosphorus is 50-150 mg / L.

3. The method according to claim 1, characterized in that, When adjusting the pH of the ultrasonic treatment solution, a sodium carbonate and sodium bicarbonate buffer solution is used.

4. The method according to claim 1, characterized in that, The magnesium source is selected from one or more of magnesium chloride, magnesium sulfate, and magnesium carbonate.

5. The method according to claim 1, characterized in that, The molar ratio of magnesium in the magnesium source to total phosphorus in the ultrasonic treatment liquid is (0.8-1.2):(1.0-1.5).

6. The method according to claim 1, characterized in that, The crystallization reaction time of the struvite is 15-25 minutes.

7. The application of the method for improving the crystallization rate and purity of struvite based on ultrasonic pretreatment as described in any one of claims 1-6 in the high-value recovery of nitrogen and phosphorus from landfill leachate.

Citation Information

Patent Citations

  • Device and method for reinforcing crystallization and dephosphorization of novel crystal seeds on basis of ultrasonic technology

    CN102745851A

  • Method for improving struvite crystal purity in landfill leachate treatment process

    CN118343722A

  • Method for stepwise and efficiently purifying key impurity sodium oxalate in sodium aluminate solution by utilizing ultrasonic waves

    CN119490213A